Evidências sobre o diamino fluoreto de prata: ensino no Brasil e influência em parâmetros restauradores - Fröhlich, Tatiana Tambara (2021)
This thesis comprises three studies focusing on silver diamine fluoride (SDF) teaching and use, and its effect on dental tissues and restorations after its use. Article 1: Teaching and using silver diamine fluoride in pediatric dentistry: a questionnaire-based cross-sectional analysis of undergraduate Brazilian dental schools. The aim of this study was to present an overview of the teaching and use of SDF in the in Pediatric Dentistry in undergraduate Brazilian dental schools. Questionnaires with questions regarding the teaching and use of SDF were sent by e-mail to the responsible for Pediatric Dentistry courses. The data obtained were analyzed descriptively and using the chi-square test. In most of the evaluated courses, SDF theoretical class topic, but its use in clinical practice is infrequent. SDF has been used mainly in cavitated caries lesions in primary teeth of children aged 0 to 3 years, with its use is restricted to posterior teeth. Article 2: Bonding of glass-ionomer cement and adhesive systems to silver diamine fluoride-treated dentine: an updated systematic review and meta-analysis. This study updated a systematic review on the influence of the previous application of SDF on the bonding or adhesive systems (AS) and glass ionomer cement (GIC), to sound and caries-affected dentin. Eleven new studies were added to the 11 previous studies, and 21 studies in the meta-analysis. Dentin pretreatment with SDF did not influence GIC adhesion, regardless of dentin condition. Treatment with SDF significantly impaired the bond strength of SA. However, the rinsing step after SDF application eliminates this negative effect on sound dentin and may increase the adhesion to caries-affected dentin. Article 3: Evaluation of the use of potassium iodide application on stained demineralized dentin under resin composite following silver diamine fluoride application. This study evaluated the effect of potassium iodide (KI) after the SDF on the staining of demineralized dentin covered or not by a layer of composite resin. For this, 30 dentin blocks were prepared, demineralized, and randomly allocated into three groups (n = 10): 1) control (without treatment); 2) treated with SDF, and 3) treated with SDF and KI. Half of the specimens in each group received a composite resin restoration immediately after treatment. The color parameters were evaluated, with a spectrophotometer, at the beginning of the study and after 7, 14, 30, and 60 days. The data were analyzed using a generalized linear model. The use of potassium iodide minimizes the darkening of dentin and prevents the staining of the dentin under composite resin restorations in the long-term. SDF is a teaching topic in undergraduate Pediatric Dentistry schools in Brazil, and its use does not interfere in the adhesion of SA and CIV and, associated with KI, in the color of composite resin restorations.